Education for solidarity at home (Journal of Parents and Teachers, 2014)
This article starts talking about the non-solidarity to continue talking about pedagogical benefits of solidarity because it prevents antisocialization, improves the personal development, involves us to share and helps us build our identity. The article goes on with a simple stage planning to develop within the family and ends up with the explanation of several discipline strategies to promote solidarity.
Keywords: KEY WORDS; family and education; education for solidarity; mediation; social behaviours.